Prevalence of depression, anxiety and post-traumatic stress in war- and conflict-afflicted areas: A meta-analysis - Lim, Isis Claire Z. Y.; Tam, Wilson W. S.; Chudzicka-Czupała, Agata; McIntyre, Roger S.; Teopiz, Kayla M.; Ho, Roger C.; Ho, Cyrus S. H. (Frontiers in Psychiatry, 2022)
Background With the rise of fragility, conflict and violence (FCV), understanding the prevalence and risk factors associated with mental disorders is beneficial to direct aid to vulnerable groups. To better understand mental disorders depending on the population and the timeframe, we performed a systematic review to investigate the aggregate prevalence of depression, anxiety and post-traumatic stress symptoms among both civilian and military population exposed to war. Methods We used MEDLINE (PubMed), Web of Science, PsycINFO, and Embase to identify studies published from inception or 1-Jan, 1945, to 31-May, 2022 (whichever earlier), to reporting on the prevalence of depression, anxiety and post-traumatic stress symptoms using structured clinical interviews and validated questionnaires as well as variables known to be associated with prevalence to perform meta-regression. We then used random-effects bivariate meta-analysis models to estimate the aggregate prevalence rate. Results The aggregate prevalence of depression, anxiety and post-traumatic stress during times of conflict or war were 28.9%, 30.7% and 23.5% respectively. Our results indicate a significant difference in the levels of depression and anxiety, but not post-traumatic stress, between the civilian group and the military group respectively (depression 34.7% vs 21.1%, p<0.001; anxiety 38.6% vs 16.2%, p<0.001; post-traumatic stress: 25.7% vs 21.3%, p=0.256). The aggregate prevalence of depression during the wars was 38.7% (95%CI: 30.0-48.3, I2=98.1%), while the aggregate prevalence of depression post-wars was 29.1% (95%CI: 24.7-33.9, I2=99.2%). The aggregate prevalence of anxiety during the wars was 43.4% (95%CI: 27.5-60.7, I2=98.6%), while the aggregate prevalence of anxiety post-wars was 30.3% (95%CI: 24.5-36.9, I2=99.2%). The subgroup analysis showed significant difference in prevalence of depression, and anxiety between the civilians and military group (p<0.001). Conclusion The aggregate prevalence of depression, anxiety and post-traumatic stress in populations experiencing FCV are 28.9%, 30.7% and 23.5% respectively. There is a significant difference in prevalence of depression and anxiety between civilians and the military personnels. Our results show that there is a significant difference in the prevalence of depression and anxiety among individuals in areas affected by FCV during the wars compared to after the wars.